The Effect of Online Brand Experience and Online Brand Community on Brand Leadership in E-Commerce: The Role of Brand Relationship Quality - Khamwon, Anon; Kumgliang, Oranich (International Review of Management and Marketing, 2025)
This research focused on studying the influence of online brand experiences and online brand communities on brand leadership through the role of an intermediary in brand relationship quality on e-commerce business context. The data were collected using an online questionnaire with 400 Thai consumers and analyzed using structural equation model analysis. The results showed that the online brand experience, directly and indirectly, influences brand leadership through brand relationship quality. At the same time, online brand communities indirectly influence brand leadership through brand relationship quality. The research results could explain 88% of the relationship with brand leadership, which e-commerce businesses can apply as a guideline for online marketing in the current era.